BERT Model Fine-tuned for Scientific Document Classification and Recommendation - Muhammad Deagama Surya Antariksa; Aris Sugiharto; Bayu Surarso (Ikatan Ahli Informatika Indonesia (IAII), 2025)
The increasing number of academic documents requires efficient and accurate classification and recommendation systems to assist in retrieving relevant information. This system is built using the